Teacherâs Competencies on the Management of Science Laboratory Public Secondary School Pekanbaru Academic Year 2014/2015 - Suryanti, Suryanti; Hidayati, Nurkhairo (Proceeding International Conference on Global Resource Conservation, 2015)
This research was conducted in order to determine the teacherâs competencies on management of science laboratory based on Permendiknas no. 26/2008 in Pekanbaru City for academic year 2014/2015. Subjects in this study are science teachers who manage science laboratories of secondary schools in Pekanbaru City. The numbers of subjects are 29 people from Public Secondary School in Pekanbaru City. Collecting data in this study was conducted by questionnaire, interview, and observation (The data analyzed descriptively and the unit measurement on analysis technique that used in this study is percentage.) From the research, its known that personal competence categorized as very competentÂ with percentage of 91.01%. Social competence is 89.90% categorized as very competent. Competence of administration is 86.74%. Then the professional competence 86.64% categorized as very competent. Competence managerial categorized as very competent (86%). It can be concluded that level of competence in management of the science lab teachers at Pekanbaruâs Public Secondary Schools for Academic Year 2014/2015 are very competent.Keywords: Management of science laboratory; public secondary school; teacher competencies